Adaptive design of tipping bucket flow meters for continuous runoff measurement - Schwamback, Dimaghi; Persson, Magnus; Berndtsson, Ronny; Anache, Jamil A. A.; Wendland, Edson Cezar (Frontiers in Environmental Science, 2023)
Runoff measurement and monitoring is a laborious, time-consuming, and costly task. Additionally, common runoff monitoring usually primarily provide water level, requiring information on the stage-discharge relation. Automatic equipment such as flow meter tipping bucket (TB) is a potential option to simplify and provide continuous runoff monitoring in small catchments. However, a proper description of how to size and adapt the design under different flow conditions is still lacking. In this paper we present a novel standardized framework for the design of TB that can be used for low-cost and real-time runoff monitoring under many different conditions. The framework consists of an estimation of the runoff peak rate using the rational equation and a volumetric capacity estimate of the cavity based on runoff rate, operation speed, and inclination angle of TB when at resting position. The proposed framework was implemented in a case study where four TBs were designed for continuous runoff monitoring from experimental plots (100 m²) with different land use (sugarcane, soybean, and bare soil). During field tests (five months), the designed TBs had a recovery rate of actual runoff ranging from 61% to 81% and were able to capture features poorly studied (starting/ending time and peak flow) that have potential importance in hydrological models. The proposed framework is flexible and can be used for different environmental conditions to provide continuous runoff data records.